Nilai-nilai Pendidikan Dalam Kesenian Randai Pada Sanggar Al-Barokah Di Korong Rimbo Panjang, Padang Pariaman - Geubrina Suci Agustin; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2021)
This study aims to identify and describe the values of Randai art education in the Al-Barokah Korong Rimbo Panjang Studio, Nagari Sungai Abang, Lubuk Alung District, Padang Pariaman Regency which is contained in the three elements of art in Randai namely script, motion, and music. The Randai played in the research object of the Al-Barokah studio is Randai with a script entitled Siti Baheram dari Pariaman, the values seen in this Randai are social values, ethics, and customs. This research is motivated by an interest in the Minangkabau tribe which is rich in customs and culture that regulates people's lives in a very complex manner. One of the elements of culture is art and a very interesting art in Minangkabau is Randai. According to Randai experts, apart from being an entertainment, it can also function as an educational medium. This research is qualitative by using descriptive method. The instrument in this study was the researcher himself with the help of stationery and cellphone cameras. Data collection techniques are observation, interviews, and documentation. The results of the study reveal that social values, ethics, and customs are contained in Siti Baheram's script, movements and in Randai music.